Farmers’ perceptions of dairy cattle breeds, breeding and feeding strategies: A case of smallholder dairy farmers in western Kenya - Lukuyu, Margaret N.; Gibson, John P.; Savage, D.B.; Rao, E.J.O.; Ndiwa, Nicholas N.; Duncan, Alan J. (Informa UK Limited, 2019)
To understand farmers' preference and perceptions of breed attributes, breeding and feeding practices, 419 households in western Kenya were interviewed in a cross-sectional survey. Respondents scored their preference for cattle breeds, traits and breeding methods on a scale of 1 (most preferred) to 5 (least preferred). Preferences were compared using multinomial logistic regression models on weighted scores. The Ayrshire breed was most preferred followed by the Friesian. Using hardship tolerance as a reference trait, the Friesian was preferred 4.86 times more for high milk production and Ayrshire, Jersey and Guernsey breeds 4.61, 4.60 and 4.18 times (p < 0.01) more, respectively, for milk fat content. The Ayrshire was preferred 4.16 times more for its perceived low feed requirement and 1.22 times more (p < 0.01) for resistance to diseases. Friesian was the only breed preferred (3.18 times more) (p < 0.01) for high growth rate of calves. Artificial insemination (AI) was the breeding method of choice, but majority (>68%) of respondents used natural mating, because it was readily available and cheaper. The current study highlights the importance of taking into account farmers' objectives and the production environment when designing breed improvement programmes and recommends packaging of breeding together with feeding interventions.